The assessment of airway maneuvers and interventions in university Canadian football, ice hockey, and soccer players - Delaney, J. S.; Al-Kashmiri, A.; Baylis, P.-J.; Troutman, T.; Aljufaili, M.; Correa, J. A. (Journal of Athletic Training, 2011)
Context: Managing an airway in an unconscious athlete is a lifesaving skill that may be made more difficult by the recent changes in protective equipment. Different airway maneuvers and techniques may be required to help ventilate an unconscious athlete who is wearing full protective equipment.